2022
DOI: 10.3390/pharmaceutics14071469
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Alterations in pH and K+ Modify the Murine Brain Endothelial Cell Total and Phospho-Proteome

Abstract: Pathologies of the blood–brain barrier (BBB) have been linked to a multitude of central nervous system (CNS) disorders whose pathology is poorly understood. Cortical spreading depression (CSD) has long been postulated to be involved in the underlying mechanisms of these disease states, yet a complete understanding remains elusive. This study seeks to utilize an in vitro model of the blood–brain barrier (BBB) with brain endothelial cell (b.End3) murine endothelioma cells to investigate the role of CSD in BBB pa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…This same group also showed that HSP90 inhibition prevented a reduction in TJ proteins occludin and ZO-1 [36]. Previously, we reported that CSD induction with cortical injection of KCl does not significantly change detection of TJ proteins (i.e., claudin 5) in cortex or brainstem as compared to aCSF controls [11]; however, KCl pulse decreases corrected total cell fluorescence of claudin 5 as compared to controls in bEnD.3 cells, but no significant changes in the surface levels of claudin 5 were observed after KCl treatment [23].…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…This same group also showed that HSP90 inhibition prevented a reduction in TJ proteins occludin and ZO-1 [36]. Previously, we reported that CSD induction with cortical injection of KCl does not significantly change detection of TJ proteins (i.e., claudin 5) in cortex or brainstem as compared to aCSF controls [11]; however, KCl pulse decreases corrected total cell fluorescence of claudin 5 as compared to controls in bEnD.3 cells, but no significant changes in the surface levels of claudin 5 were observed after KCl treatment [23].…”
Section: Discussionmentioning
confidence: 83%
“…We have previously observed that high extracellular K + promotes ZO-1 phosphorylation in bEnd.3 endothelial cells. Thus, 17-AAG may be preventing ZO-1 degradation to indirectly increase detection of claudin 5 [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Low gravity simulation and spaceflight have been shown to negatively impact the blood-brain barrier. Proteomics showed alterations in the expression of cell-cell adhesion molecules and Zonula occludins-1, a key component of tight junctions [226].…”
Section: Cell-cell Adhesions and Tight Junctions In Low Gravitymentioning
confidence: 99%
“…Progenesis QI for proteomics software (version 2.4, Nonlinear Dynamics Ltd., Newcastle upon Tyne, UK) was used to perform ion-intensity based label-free quantification as previously described [63][64][65][66]. In brief, in an automated format, .raw files were imported and converted into two-dimensional maps (y-axis = time, x-axis = m/z) followed by the selection of a reference run for alignment purposes.…”
Section: Label-free Quantitative Proteomicsmentioning
confidence: 99%